THE LATENT PERIOD OF SOME OF SPECIES OF THE GENUS MALUS INTRODUCED IN THE PETER THE GREAT BOTANICAL GARDEN - K. G. Tkachenko (Труды по прикладной ботанике, генетике и селекции)
The presence of the resulting fruit and mature seeds of introduced plants - one of the indicators of the success of introduction of new types of tests in specific climatic conditions. The study of the latent period and the evaluation of the quality of reproductive diaspora are necessary to develop recommendations for the implementation of promising species for the needs of the national economy and the urban and landscape gardening. This assessment is important for collections of the Botanical Gardens, as they participate in the international exchange of seeds, and it is always important to know - what quality seeds are sent or received in the garden upon request. The purpose of this work - assessment of the quality of seeds of some species of apple tree Malus Mill. (Rosaceae), introduced in the Peter the Great Botanical Garden. In the course of the work it is shown that in the conditions of St. Petersburg, a considerable number of introduced species of fruit each year form a complete and viable seeds. It was found that different types of apples are not all the fruits of the seeds are formed, and many formed seeds are damaged by pests. That less, for seed multiplication, you can use the seeds of its own reproduction, but only after a careful selection of the most large and made of them not affected by pests. It is necessary to carry out preventive measures to fumigation reproductive dias-poras for timely pest control.